Chlorophyll a crude extract: efficient photo-degradable photocatalyst for PET-RAFT polymerization. Issue 93 (8th November 2017) - Wu, Chenyu; Shanmugam, Sivaprakash; Xu, Jiangtao; Zhu, Jian; Boyer, Cyrille
Abstract : This work demonstrates use of spinach extracts for living radical polymerization bypassing catalyst synthesis/purification, degassing and catalyst removal procedures. Abstract : We investigated the use of crude chlorophyll extracts to catalyze photoinduced electron/energy transfer-reversible addition–fragmentation chain transfer (PET-RAFT) polymerization under red light irradiation. We discovered that Chl a degrades under visible light in the presence of air, which can eliminate the need for catalyst removal after polymerization.